Trypanosoma brucei brucei Induces Polymorphonuclear Neutrophil Activation and Neutrophil Extracellular Traps Release - Grob, Daniela; Conejeros, Iván; Velásquez, Zahady D.; Preußer, Christian; Gärtner, Ulrich; Alarcón, Pablo; Burgos, Rafael A.; Hermosilla, Carlos; Taubert, Anja (Frontiers in Immunology, 2020)
T. b. brucei trypomastigotes are classical blood parasites of cattle, these stages might become potential targets for circulating polymorphonuclear neutrophils (PMN). We here investigated NETs extrusion and related oxygen consumption in bovine PMN exposed to motile T. b. brucei trypomastigotes in vitro. Parasite exposure induced PMN activation as detected by enhanced oxygen consumption rates (OCR), extracellular acidification rates (ECAR), and production of total and extracellular reactive oxygen species (ROS). Scanning electron microscopy (SEM) showed that co-cultivation of bovine PMN with motile trypomastigotes resulted in NETs formation within 120 min of exposure. T. b. brucei-induced NETs were confirmed by confocal microscopy demonstrating co-localization of extruded DNA with neutrophil elastase (NE) and nuclear histones. Immunofluorescence analyses demonstrated that trypomastigotes induced different phenotypes of NETs in bovine PMN, such as aggregated NETs (aggNETs), spread NETs (sprNETs) and diffuse NETs (diffNETs) with aggNETs being the most abundant ones. Furthermore, live cell 3D-holotomographic microscopy unveiled detailed morphological changes during the NETotic process. Quantification of T. b. brucei-induced NETs formation was estimated by DNA and nuclear area analysis (DANA) and confirmed enhanced NETs formation in response to trypomastigote stages. Formation of NETs does not result in a decrease of T. b. brucei viability, but a decrease of 26% in the number of motile parasites. Referring the involved signaling pathways, trypomastigote-induced NETs formation seems to be purinergic-dependent, since inhibition via NF449 treatment resulted in a significant reduction of T. b. brucei-triggered DNA extrusion. Overall, future studies will have to analyze whether the formation of aggNETs indeed plays a role in the outcome of clinical disease and bovine African trypanosomiasis-related immunopathological disorders, such as increased intravascular coagulopathy and vascular permeability, often reported to occur in this disease.